Prescribing of long‐acting reversible contraception by general practice registrars across different rural regions of Australia: A cross‐sectional analysis of the Registrar Clinical Encounters in Training Study data. (20th June 2021) - Turner, Rachel; Tapley, Amanda; Sweeney, Sally; Davey, Andrew; van Driel, Mieke; Morgan, Simon; Spike, Neil; FitzGerald, Kristen; Magin, Parker
Abstract: Objective: To describe the pattern of prescribing long‐acting reversible contraception by Australian general practitioner registrars across different classifications of rurality/urbanicity. Methods: A study nested within the Registrar Clinical Encounters in Training ongoing cohort study of Australian general practitioner registrars' in‐consultation experience. Design: A cross‐sectional analysis of Registrar Clinical Encounters in Training data collected 2010‐2017. Type of contraception prescribed by general practitioner registrars to women aged 12‐55 for contraception‐related indications was documented. Chi‐square statistical analysis was performed to assess association of specific long‐acting reversible contraception methods with rurality/urbanicity. Setting/Participants: General practitioner registrars enrolled in the Australian General Practice Training program in regional training providers/organisations participating in Registrar Clinical Encounters in Training. Main outcome measures: Long‐acting reversible contraception was defined as etonogestrel implant, copper intrauterine device, levonorgestrel intrauterine device and medroxyprogesterone injection. Results: In all 1737 registrars recorded 4073 registrar rounds of data from 2010 to 2017 (response rate 96%). Type of long‐acting reversible contraception prescribed differed significantly across Australian Statistical Geography Standards classification of rurality (Pearson's χ 2  = 17, P  = .002). Women living in outer regional/remote/very remote regions are prescribed proportionately more medroxyprogesterone injection and less levonorgestrel intrauterine device compared to major cities/inner regional areas. Conclusions: Long‐acting reversible contraception methods prescribed differ across different classifications of rurality. Women living in more rural/remote regions might have access difficulties for the levonorgestrel intrauterine device.